The significance of the command verb and the compatibility of the Quranic comma - Almahaijri, Saad Faiz Khamis (Journal of Arabic Language Sciences and Literature, 2023)
This research takes a different approach to a linguistic aspect that has been discussed in the Arabic language, which is the imperative verb (command verb). When we mention the "Qur’anic comma," it is necessary for the interpreters to be present in this research. This contrasting approach comes through the analytical examination of using one imperative verb over another, synonymous with it in a specific context. It explores the linguistic indicators associated with using this verb with the Qur’anic comma, other words within the same verse, or a specific context, all aiming to maintain a specific semantic unity without compromising meaning, pronunciation, structure, appropriateness, or occasion of revelation. Some of these implications have been mentioned in the works of linguists and interpreters without referring to their relationship with the linguistic root, whether related to the verb or the Qur’anic comma. The significance of the linguistic root of the word is considered one of the fundamentals of semantic guidance for the Qur’anic meaning and cannot be disregarded under any circumstances. This research focuses on the imperative verb in its direct form and its significance .It provides Quranic examples of using imperative verbs and explains the specific uses and their compatibility with Quranic comma after analyzing their linguistic root.